2012
DOI: 10.1111/j.1532-950x.2012.01015.x
|View full text |Cite
|
Sign up to set email alerts
|

Complications and Owner Assessment of Canine Total Hip Replacement: A Multicenter Internet Based Survey

Abstract: The BVOA-CHR offers a novel framework for the prospective studies on THR and on a national/international scale. Initial complication rates from the BVOA-CHR are similar to previous studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
78
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(90 citation statements)
references
References 17 publications
12
78
0
Order By: Relevance
“…Success rates for either cemented or cementless THR have been reported at 80–98 per cent based on both clinical and radiographic evaluation of pain status and functionality, and owner assessment (Olmstead and others 1983, Olmstead 1987, 1995, DeYoung and others 1992, 1993, Massat and Vasseur 1994, Marcellin-Little and others 1999, Skurla and others 2000). Previous results obtained from the BVOA-CHR revealed that in 94 per cent of cases owners described their satisfaction with the outcome of THR as ‘very good’ or ‘good’ (Forster and others 2012). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Success rates for either cemented or cementless THR have been reported at 80–98 per cent based on both clinical and radiographic evaluation of pain status and functionality, and owner assessment (Olmstead and others 1983, Olmstead 1987, 1995, DeYoung and others 1992, 1993, Massat and Vasseur 1994, Marcellin-Little and others 1999, Skurla and others 2000). Previous results obtained from the BVOA-CHR revealed that in 94 per cent of cases owners described their satisfaction with the outcome of THR as ‘very good’ or ‘good’ (Forster and others 2012). …”
Section: Introductionmentioning
confidence: 99%
“…The BVOA-CHR offers an ongoing follow-up on all cases submitted, whereby surgeons are encouraged to document complications as and when necessary, months or even years after surgery. A previous report by Forster and others (2012) describes 170 cases of THR. Continued submission of complications associated with these cases can occur and therefore enables long-term complications of THR to be reported.…”
Section: Introductionmentioning
confidence: 99%
“…Possible complications of this technique are hemorrhage, sciatic nerve damage, pin loosening, pin track drainage and disruption of the flexible band [9,31] . Additionally, total hip replacement [22][23][24] and femoral head and neck osteotomy [2,25,26] can be also BELGE, BOZKAN, SARIERLER, YAYGINGÜL applied for the treatment of hip luxation, however these techniques are usually preferred, if there is degenerative joint disease. In a multicenter internet based study on assessment of canine total hip replacement in 170 dogs, there were only 6 dogs which applied total hip replacement with coxofemoral luxation treatment indication [24] .…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, total hip replacement [22][23][24] and femoral head and neck osteotomy [2,25,26] can be also BELGE, BOZKAN, SARIERLER, YAYGINGÜL applied for the treatment of hip luxation, however these techniques are usually preferred, if there is degenerative joint disease. In a multicenter internet based study on assessment of canine total hip replacement in 170 dogs, there were only 6 dogs which applied total hip replacement with coxofemoral luxation treatment indication [24] . Lower complication rate, higher clinical healing rate [8,13,30,[34][35][36] and also 0 to 6% reluxation rate based on small number case series [14,34] has been reported on synthetic capsule technique.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation